2010
DOI: 10.1371/journal.pone.0013626
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-15 Polymorphisms in Adult Acute Lymphoblastic Leukemia

Abstract: BackgroundInterleukin-15 (IL-15) plays important roles in the immune system and in the development of hematopoietic cells. Previous studies revealed that five SNPs in IL-15, rs10519612, rs10519613, rs35964658, rs17007695 and rs17015014, were significantly associated with childhood Acute Lymphoblastic Leukemia (ALL) treatment response. In adult ALL, the expression of IL-15 was also correlated with the immunophenotypes of ALL. Therefore, we hypothesize that SNPs of IL-15 might also be associated with adult ALL.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…IL15 can induce survival and proliferation of growth factor-dependent AML cells through interaction with IL2 receptor beta/gamma [69], and its upregulation may be a predictor of disease relapse in pediatric AML patients [70]. Moreover, single nucleotide polymorphisms in the IL15 gene have been associated with risk of developing adult acute lymphoblastic leukemia [71]. These studies highlight the potential relevance of IL15 targeting in therapies for hematopoietic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…IL15 can induce survival and proliferation of growth factor-dependent AML cells through interaction with IL2 receptor beta/gamma [69], and its upregulation may be a predictor of disease relapse in pediatric AML patients [70]. Moreover, single nucleotide polymorphisms in the IL15 gene have been associated with risk of developing adult acute lymphoblastic leukemia [71]. These studies highlight the potential relevance of IL15 targeting in therapies for hematopoietic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…59 In adult ALL, the expression of IL-15 has also been correlated with the immunophenotypes of ALL, therefore Lin et al genotyped the five SNPs of the IL-15 gene by polymerase chain reaction -restriction fragment length polymorphism assays and observed a excess risk of developing ALL for the rs10519612 CC and rs17007695 TC genotype carriers in the adult Chinese population. 60 Aly et al also observed a higher risk of developing T-cell ALL for rs10519612 CC and an increased risk of developing B-cell ALL for rs17007695 TC and rs17007695 CC genotype carriers in Egypt. 61 These results suggested that several IL-15 SNPs, which were associated with minimal residual disease and correlated with the immunophenotypes of ALL, may provide important prognostic information in ALL patients.…”
Section: Allmentioning
confidence: 93%
“…Several large observational studies have linked interleukin-15 (IL-15) singlenucleotide polymorphisms (SNPs) or mRNA levels to aspects of acute lymphoblastic leukemia (ALL) biology. Two independent genome-wide association studies (GWAS) identified polymorphisms in the IL-15 gene as predictors of leukemia development 1 and resistance to initial therapy. 2 Microarray data suggest that IL-15 mRNA levels predict the likelihood of central nervous system (CNS) relapse in childhood ALL.…”
Section: Introductionmentioning
confidence: 99%